Upaya Peningkatan Pengetahuan Serta Penerapan Perilaku Hidup Bersih dan Sehat pada Ibu Balita Stunting - Prawesty D. Utami; Retno Budiarti; Herin Setianingsih; Pramita A. Nugraheni; Wahyu P. Mutiadesi; Annisa U. Rasyida; Mita Herdiyanti; Ronald P. Adiwinoto (Syntax Literate, 2023)
Stunting or stunted toddlers are a national health issue that jeopardizes a generation's survival. Infection is one of the risks that stunted toddlers frequently face. Promoting learning and adopting healthy and clean lifestyle practices (PHBS) are two ways to lower the risk of illness. This cross-sectional, analytical observational study was carried out in the Ngagel Rejo Community Health Center in Surabaya, East Java, in Indonesia. A questionnaire assessed mothers with stunted toddlers' knowledge and application of PHBS before and after education. Efforts to increase knowledge and implementation of PHBS are being made by educating mothers of stunted toddlers. Indicators of PENMAS activities’ success include the participation of mothers of stunted toddlers of at least 70%, increased knowledge, and implementation of PHBS of at least 20%. Knowledge and application of PHBS of mothers of stunted toddlers were assessed using a questionnaire before and after providing education. The achievement of PENMAS activities exceeded the success indicators, with PENMAS participants by 89.13% (above the target of 70%), a rise in PHBS application by 41.30%, a rise in PHBS knowledge by 31.23% (over the aim of 20%). Considering on these findings, it can be stated that this PENMAS activity might assist mothers of toddlers with stunting to raise their level of awareness and PHBS application, so that it is expected to prevent morbidity and mortality rates of stunting toddlers in the Ngagel Rejo Surabaya Puskesmas area.